Bombay to Mumbai : changing perspectives - Rohatgi, Pauline; Godrej, Pheroza; Mehrotra, Rahul; Ramamrutham, Bharath; Marg Publications ([Mumbai] : Marg Publications, 1997)
Contributed articles.
Includes bibliographical references (p. [10]-[11], last group) and index.
Keywords: Mumbai (India); Mumbai (India) -- Pictorial works